Measuring empowerment : cross-disciplinary perspectives (World Bank, 2005)
"Measuring Empowerment is an invaluable resource for planners, practitioners, evaluators, and students - indeed for all who are interested in approaches to poverty reduction that address issues of inequitable power relations."--BOOK JACKET.